REPUBLIC OF BELARUS ON EUROPEAN ARENA - P. V. Baykov (Nauka i Tehnika, 2008)
The paper analyzes stages of interrelations between theRepublicofBelarusand European Union. Strategic directions of Belarusian foreign economic policy are determined for coming years. A number of measures for creation of economic cooperation model are proposed in the paper.